2006
DOI: 10.1001/archpsyc.63.8.856
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of an N-methyl-D-aspartate Antagonist in Treatment-Resistant Major Depression

Abstract: Robust and rapid antidepressant effects resulted from a single intravenous dose of an N-methyl-D-aspartate antagonist; onset occurred within 2 hours postinfusion and continued to remain significant for 1 week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

101
2,273
12
58

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 3,282 publications
(2,444 citation statements)
references
References 55 publications
101
2,273
12
58
Order By: Relevance
“…Preclinical and clinical studies have reported that low doses of the noncompetitive NMDAR antagonist and psychotomimetic ketamine have a rapid antidepressant action: a rapid (within hours) and sustained (up to 1 week) antidepressant effect on core symptoms can be induced by a single subanesthetic dose of intravenously-infused ketamine in patients with treatment-resistant depression [7,8,14,111] .…”
Section: Ketamine Has Rapid-onset Antidepressant Effi Cacymentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical and clinical studies have reported that low doses of the noncompetitive NMDAR antagonist and psychotomimetic ketamine have a rapid antidepressant action: a rapid (within hours) and sustained (up to 1 week) antidepressant effect on core symptoms can be induced by a single subanesthetic dose of intravenously-infused ketamine in patients with treatment-resistant depression [7,8,14,111] .…”
Section: Ketamine Has Rapid-onset Antidepressant Effi Cacymentioning
confidence: 99%
“…Thus, the mechanisms underlying the clinical response to antidepressants may include effects on neural plasticity. This point of view is strongly supported by the rapid onset of antidepressant efficacy of ketamine in clinical trials, because NMDAR activation is critical for both LTP and hippocampusdependent memory [8,13,14] . These developments suggest an alternative etiology for depression due to functional disturbances of neural plasticity in the glutamatergic system.…”
mentioning
confidence: 94%
“…Response rates for initial treatment are estimated to be about 50%, while remission, considered to be the goal of treatment, ranges from 15–40% 1. The metabotropic glutamate receptor 5 (mGlu5) receptor has emerged as an attractive target for the treatment of anxiety and depressive disorders based on its expression pattern in the brain and the efficacy of mGlu5 antagonists in various animal models 2, 3. Glutamate is the main excitatory neurotransmitter that mediates its effects via ionotropic glutamate receptors (i.e., N‐methyl‐D‐aspartate (NMDA), α‐amino‐3‐hydroxy‐5‐methylisoazol‐4‐priopionate (AMPA) or kainate receptors) and G‐protein‐coupled receptors (e.g., mGlu receptors).…”
mentioning
confidence: 99%
“…Ketamine is a noncompetitive N-methyl-D-aspartate receptor (NMDAR) antagonist that has attracted widespread attention for its rapid-onset antidepressant effects, especially in individuals with treatment-resistant depression and suicidal ideation [1][2][3]. Compared with the traditional antidepressants that take weeks, if not months, to benefit patients and are associated with a high rate of relapse, ketamine exerts its antidepressant effects within several hours.…”
mentioning
confidence: 99%
“…Compared with the traditional antidepressants that take weeks, if not months, to benefit patients and are associated with a high rate of relapse, ketamine exerts its antidepressant effects within several hours. These clinical benefits can last for 2 weeks after a single injection [1,2,4]. However, ketamine still has limited clinical application, mainly because of its psychotomimetic side-effects and liability of abuse.…”
mentioning
confidence: 99%